ANALYSIS OF VEGETATION DENSITY IN FLOOD DISASTER USINGLANDSAT 8 IMAGERY IN JEMBER URBAN AREA 2010-2019 AND 2020-2022 - Amrullah, Muhammad Jiddan; Anggita, Sofia; Oktivia Puteri, Syafira Alifah; Tobing, Ully Amalia; Pangastuti, Era Iswara; Mujib, Muhammad Asyroful (Indonesian Journal of Remote Sensing and Applications, 2023)
Vegetation has an important in human life. Studies related to vegetation can include its density or distribution in the area. To analyze the vegetation density in an area by using Remote Sensing System technology. This study aims to analyze vegetation density in flood disaster using Landsat 8 imagery in the urban area of Jember in 2010-2019 and 2020-2022. The research method used is a quantitative research method. This type of research was chosen because there will be data that needs to be processed using remote sensing techniques, which are also related to numbers. The research object to be studied is vegetation density using Landsat 8-OLI imagery and field survey data. The data collection technique in this study uses the observation method to compare the results of imagery processing on the Envi 4.5 application with direct conditions in the field, then field documentation is carried out. Then the vegetation index method used is the NDVI method (Normalized Difference Vegetation Index). The results of the research it is known that several sub-districts in the center of Jember Regency, such as Patrang, Sumbersari, and Kaliwates sub-districts, have land cover for vegetation that varies from medium to dense vegetation.